Developing the Interest of Group A Children of Abdan Syakuro Kindergarten, South Tangerang City, in Various Pattern Cutting Activities - Fatin, Amalia Madina (USN Kolaka, 2024)
This research aims to develop children's interest in drawing varied patterns in group A of Abdan Syakuro Kindergarten. Fine motor skills are an essential aspect that must be developed from an early age. One learning activity that can develop fine motor skills is cutting. Cutting activities can be a child's initial writing stage, especially when holding a pencil. For this reason, we as educators must have exciting and fun learning methods. This research used the classroom action research method at Kindergarten A Abdan Syakuro, totalling nine children. This research was carried out through the initial/observation stages, cycles I and II. It can be seen from the learning results from cycle 1 to cycle two that children have improved. Pattern-cutting activities can develop children's interest in cutting.